Risk Factors of Cognitive Impairment Post Ischemic Stroke - Nurani, Rr Rizqi Saphira; Martini, Santi; Marzela, Fanni (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
The aim of this research was to analyze the risk factors of cognitive impairment post-ischemic stroke. This research was case control design, consisted of 38 cases and 38 control. Mini Mental State Examination (MMSE) and the Pittsburg Sleep Quality Index (PSQI) were tools to obtain data. Independent variables were age, gender, educational level, history of hypertension, exposure to cigarette smoke, medication compliance, and sleep pattern. The risk factors were age (OR = 3,43; 95% CI = 1,08<OR<10,89), sex (OR = 2,67; 95% CI = 1.05<OR<6,83), educational level (OR = 4,17; 95% CI = 1,60<OR<10,86), history of hypertension (OR = 1,60; 95% CI = 0,62<OR<4,17), exposure to cigarette smoke (OR = 1,24; 95% CI = 0,50<OR<3,04), medication compliance (OR = 6,59; 95% CI = 2,23<OR<19,43), and sleep pattern (OR = 8,125; 95% CI = 2,88<OR<22,93). It is suggested for ischemic stroke’s patient to maintain medication compliance and sleep pattern.